2016
DOI: 10.1111/ans.13856
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of reusable versus disposable laparoscopic instruments: costs and safety

Abstract: Further examination of cost comparisons between disposable and reusable instruments is necessary while externalized environmental costs, instrument function and safety are also important to consider in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 20 publications
(92 reference statements)
0
54
0
Order By: Relevance
“…5 Similar case studies have shown that reusable operating room linens, surgical packs, and towels provide significant cost savings compared to disposable alternatives. 1,[6][7][8] The evaluation of the comfort of isolation gowns is complex and involves human perception. Although individual features of isolation gowns have been found to affect hospital staff and visitor compliance, whether a gown is reusable or disposable has been found to have little to no impact on compliance.…”
mentioning
confidence: 99%
“…5 Similar case studies have shown that reusable operating room linens, surgical packs, and towels provide significant cost savings compared to disposable alternatives. 1,[6][7][8] The evaluation of the comfort of isolation gowns is complex and involves human perception. Although individual features of isolation gowns have been found to affect hospital staff and visitor compliance, whether a gown is reusable or disposable has been found to have little to no impact on compliance.…”
mentioning
confidence: 99%
“…It is vital to have the instruments in good condition and the correct technology to carry out the procedures successfully. The correct use of disposable or reusable devices is fundamental, and their evaluation of cost-effectiveness according to the characteristics of the institution 15 . The control and periodic review of the systems used (for example: the quality of the image provided by the monitor during a laparoscopy, the pressure and flow offered by the pneumoperitoneum system, or the power of the electrocautery, among other details), are as important as the surgeon’s skill in carrying out the operation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, traditional reusable scopes are often associated high maintenance costs, expensive sterilization process, and risks of transmission of diseases such as Creutzfeldt-Jakob DOI: 10.22374/jeleuv1i1. 5 disease. To overcome these barriers, and to provide a simpler and more straightforward solution, Coloplast ® (Humlebaek, Denmark) has developed Isiris α™ which is a single-use, disposable 16Ch flexible digital video flexible cystoscope with an integrated stent grasper (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, the cost effectiveness of such single-use, disposable medical instrument and endoscopes remains controversial and debatable. [3][4][5][6][7][8][9][10][11][12]…”
Section: Discussionmentioning
confidence: 99%